A Study on Characteristics of Brake Pad Composite Materials by Varying the Composition of Epoxy, Rice Husk, Al2O3, and Fe2O3 - Muhammad Khafidh; Finny Pratama Putera; Rahmadi Yotenka; Deni Fajar Fitriyana; Rahmat Doni Widodo; Rifky Ismail; Agustinus Purna Irawan; Tezara Cionita; Januar Parlaungan Siregar; Nur Hidayah Ismail (Automotive Experiences, 2023)
The use of composite materials in brake pads is becoming increasingly popular due to their high-performance characteristics, including good thermal stability, high wear resistance, and low noise generation. However, the development of new composite materials that offer even better performance is still an ongoing research area. In this study, the composite was made by hand layup method using epoxy resin as matrix material, with rice husk, Al2O3, and Fe2O3 as reinforcing materials. The composition of the composites was varied by changing the percentage of the reinforcement materials. The composites were then subjected to several characterization tests, including density, hardness, flexural strength, thermal analysis, Scanning Electron Microscopy (SEM), TGA/DSC, and wear testing. The test results showed that additional reinforcement materials to the epoxy resin matrix improved the mechanical properties of the composites. Overall, the study demonstrates that a hand layup method is a viable approach for preparing brake pad composite materials and that the addition of rice husk, Al2O3, and Fe2O3 can improve the mechanical properties of the composites. The best properties produced in this research were found in one of the specimens which used epoxy, rice husk, Al2O3, and Fe2O3 with a composition of 50 wt.%, 20 wt.%, 15 wt.%, and 15 wt.%. However, the addition of rice husk also provides wear resistance and thermal stability. This study contributes to the Sustainable Development Goals (SDGs) by advancing innovation, promoting sustainability, and reducing emissions in automotive industry applications.